2016
DOI: 10.1103/physrevb.94.024428
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in Fe/Au multilayers

Abstract: To understand the interfacial scattering effect on the anomalous Hall effect (AHE), we prepared multilayers of (Fe (36/n) nm /Au (12/n) nm ) n using an e-beam evaporator. This structure design allowed us to investigate the effect of interfacial scattering on the AHE, while keeping the samples' thickness and composition unchanged. We measured the (magneto)transport properties of the samples in a wide temperature range (10-310 K) with magnetic fields up to 50 kOe. We found that the scaling between the anomalous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
21
1
4
Order By: Relevance
“…21,22 Theoretical work has been reported that interfacial spin-orbit scattering could induce AMR. 23 In our previous work, 11 interfacial scattering resulted in AMR in Fe/Au multilayers due to the SOC of Au layers. Since the SOC is larger in Ta than that in Au, we then studied how the interfacial scattering affects the magnetoresistance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…21,22 Theoretical work has been reported that interfacial spin-orbit scattering could induce AMR. 23 In our previous work, 11 interfacial scattering resulted in AMR in Fe/Au multilayers due to the SOC of Au layers. Since the SOC is larger in Ta than that in Au, we then studied how the interfacial scattering affects the magnetoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…2(j). For comparison, the AMR values of the Fe/Au samples 11 were also plotted. The AMR value is defined as AMR = R (1000 Oe)−R ⊥ (1000 Oe) R ⊥ (1000 Oe) ×100%, where R (1000 Oe)[R ⊥ (1000 Oe)] is the resistivity when magnetic field parallel (perpendicular) to the measurement current at 1000 Oe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the higher magnetic state of Fe in Au-Fe than in pure Fe, various properties have been studied, including thickness dependent spin-glass behavior and anomalous hall conductivity in Fe/Au multilayers. [1][2][3][4][5] Due to its exceptional biocompatibility and favorable physical properties, Au-Fe nanoparticles find various applications in medical sciences, as a promising candidate for cancer cell treatment, multimodal magneto-resonance imaging agent, etc.. [6][7][8][9][10] Gold-rich Au-Fe alloys form a simple face-centeredcubic (fcc) structure. Although fcc is a high-temperature phase, Au-Fe alloys up to 53 at.%Fe are reported to be easily stabilized at room temperature.…”
mentioning
confidence: 99%